SURVEI KEPUASAN MASYARAKAT DALAM MENINGKATKAN PELAYANAN PUBLIK DI KANTOR DESA PADENGO KECAMATAN LIMBOTO BARAT KABUPATEN GORONTALO - Cika Yudarsi Puhi; Arifin Tahir; Juriko Abdussamad (Universitas Bina Taruna Gorontalo, 2023)
This study measured the Comunnity Satisfaction Survey in improving public services at the Padengo Village Office, West Limboto Sub-district, Gorontalo regency, this study applied a mixed method, a combination of qualitative and quantitative methods. The result of the measurement of the 9 Commmunity Satisfaction Survey indicatior included (a) Requirement with SKM (Communtiy Satisfaction Survey) score of 3,34 and in the good category, (c) Services Time with SKM score of 3,29 and in the good category, (d) Cost//tarif of 3,71 and in the good category, (e) Product specification for the type of service/service result, the SKM score was 3,23 and in the category, (f) Competency of the SKM implementer was 3,39 and in the good category, (g) Behavior of the SKM implementer was 3,21 and in he good category, (h) Complaint, and suggesting handling, with SKM implementer was 3,43 and in the good category, and (i) Facilities and Infrastructure with SKM score of 3,61 and in the good category.Based on the study, it can be concluded that that from the results of the Community Satisfaction Survey (SKM) measurement of the implementation of the office, West Limboto Sub – district, Gorontalo Regency, The SKM score was 76,67. This score was included in the GOOD “B” category according to KEPMENPAN (Ministry of administrative and Bureaucratic Reform of the Republic of Indonesia) No. 14 of 2017. Howefer, there was still a need to improve indicators of service time and behavior of village officials to be more friendly and polite to the community to achieve moer excellent service.